Atrial Septal Defect - Hakim, An Nahl Aulia; Adnaya, Anak Agung Ngurah Maheza; Prasetyo, Ananda Bangun; Pikir, Rizqi Rokhmadhoni; Diarsvitri, Wienta; Suhadi, Ananda Rizki; Dita, Anastasia (Fakultas Kedokteran, Universitas Hang Tuah, 2024)
Background: Atrial Septal Defect (ASD) is one of the most common congenital heart diseases, occurring in about 25% of children and accounting for 6-10% of all congenital heart conditions. ASD is more frequently observed in females with a ratio of 2:1 and often does not show symptoms in infants, unless there is an increase in right ventricular volume. Case Report: A 7-year-old girl was referred with complaints of shortness of breath and cyanosis at the fingertips, accompanied by palpitations. Initial diagnosis was established through physical examination and echocardiography, which revealed a secundum ASD measuring 1.9 cm. The ASD closure surgery was performed but had to be halted due to intraoperative bradycardia. The patient then underwent subsequent therapy with Lisinopril and Spironolactone and was in good condition at the last follow-up. Discussion: Management of ASD, whether through surgical or catheter-based intervention, is recommended to prevent further complications such as paradoxical embolism and pulmonary hypertension. This case underscores the importance of timely diagnosis and treatment to prevent long-term health impacts in patients with ASD.